Modelo de gerencia ágil para proyectos de investigación y desarrollo en áreas biológicas (2018)
This work is based on the need to carry out flexible management processes in Research and Development projects in biological areas, taking into account the changing environments of this type of projects, seeking to improve management processes, use of resources, compliance with the scope, objectives , time and budget. The objectives were to identify the tools and techniques of agile Scrum, Kanban and Lean agile methodologies that could be applied in the management of Research and Development projects, to characterize the management practices used by researchers in this type of projects and the design of an agile management model. With the support of researchers from national, international and multinational research centers, it was identified that it was necessary to strengthen all phases of the management process, as well as to incorporate the project formulation phase, which facilitates subsequent management processes. From this information, a life cycle of four phases was designed: Formulation, Plan-in, Agile Execution that contains the iterative cycles (Definition, Action, Reflection, Validation) and Closure. Each phase has a process that includes a sequence of activities to guide its execution, which incorporated 13 tools and techniques from three agile methodologies (Scrum, Lean agile and Kanban), applicable to these projects. This model can be applied both by leading project researchers and by the other members involved in the execution. The application of a management model can help reduce the inherent risk of research and improve decision making.